Bibliografía temática de estudios sobre el teatro español antiguo - McCready, W. T. (University of Toronto Press, 2018)
A catalog of comedies, arranged by title and by author, is also found in the Biblioteca de Autores Eaoeiioles, tanoa 47 y 49 (first published in 1858-59 and reprinted several times since), but it has never been requested and, Although useful, it should be used with caution.